PENDAMPINGAN GEMARI DAN REDARKUM MELALUI DISEMINASI â€œSTOP PERNIKAHAN DINIâ€ - hadiningrum, Lila; Zuhroh, Diana; Sabiq, Fairuz (Asosiasi Dosen PkM Indonesia, 2021)
ABSTRACT Indonesia is faced with increasing cases of early marriage globally. It is necessary to socialize the minimum age limit and the maturity of the marriage age as an insight to the community and awareness to teenagers so that in planning a family by considering various aspects related to married life. This study raises the priority issues used related to the lack of literacy related to the Marriage Age Limit in Pucang Miliran Village, Tulung, Klaten. Assistance for gemari and redarkum through the dissemination of